ANALISIS BIBLIOMETRIK TREN GLOBAL KOMUNIKASI MATEMATIKA DALAM PENDIDIKAN (1995-2023) - Allisa Madepera; Suparman, Suparman (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2024)
This research aims to provide information related to global research trends on mathematical communication. A bibliometric study was used to see the development of international articles on mathematical communication from 1995 to 2023 through the Dimensions database. This research uses a bibliometric analysis method through the flow diagram stages of Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The results of this research show that mathematical communication is still a topic of interest for research, with the article entitled “There is more to discourse than meets the ears: Looking at thinking as communicating to learn more about mathematical learning” by Anna Sfard being the article with the most citations. The most articles in the SDGs are in the field of quality education, while the AIP Conference Proceedings is the publication that contains the most mathematical communication topics. Apart from that, it is also known that Yus Mochamad Cholily is the writer with the highest productivity on the topic of mathematical communication. The terms related to mathematical communication that are most popular in research are: cognitive style, PJBL, linear equations and mathematical expression. As for future research, it is hoped that there will be a link between mathematical communication with: emotional intelligence, PjBL and initial ability. The results of the co-authorship analysis show that there is one largest cluster containing eight authors. These results can be the basis for developing further research related to mathematical communication.